1993
DOI: 10.3109/01902149309071083
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of Dexamethasone on the Activity and Synthesis of β-Galactoside Specific Lectin (Galaptin) During Postnatal Lung Development

Abstract: This study examined the regulation of the activity and synthesis of lung beta-galactoside specific lectin (galaptin) by dexamethasone (Dex). The effect of Dex was different depending on the postnatal period administered. Dex decreased galaptin activity and synthesis when administered daily during the "critical period" of alveolarization (postnatal days 3-13) described by Massaro and coworkers (J Clin Invest 76:1297-1305, 1985). The normal rise in galaptin activity (both soluble and membrane- or particulate-bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Ten-fold overexpression of this gene concurrent with onset of glucocorticoid-induced apoptosis in the susceptible human T cell leukemia line CEM C7 implicates this lectin in glucocorticoid-mediated lymphocytolysis (Goldstone and Lavin, 1991). Regulation of galectin-1 by mechanisms at the level of transcription, translation, or degradation has also been noted during postnatal rat lung development, in which stage and duration of treatment with dexamethasone were found to be critical (Clerch et al, 1987;Sandford et al, 1993). Transcriptional regulation can be attributed to the presence of a putative steroid-binding site located at Ϫ210 in the galectin-1 gene (Gitt and Barondes, 1991).…”
mentioning
confidence: 92%
“…Ten-fold overexpression of this gene concurrent with onset of glucocorticoid-induced apoptosis in the susceptible human T cell leukemia line CEM C7 implicates this lectin in glucocorticoid-mediated lymphocytolysis (Goldstone and Lavin, 1991). Regulation of galectin-1 by mechanisms at the level of transcription, translation, or degradation has also been noted during postnatal rat lung development, in which stage and duration of treatment with dexamethasone were found to be critical (Clerch et al, 1987;Sandford et al, 1993). Transcriptional regulation can be attributed to the presence of a putative steroid-binding site located at Ϫ210 in the galectin-1 gene (Gitt and Barondes, 1991).…”
mentioning
confidence: 92%
“…Steroid responsiveness is also seen for glucocorticoids in the human T cell leukemia line CEM C7 and clinical material of nasal polyps (Goldstone and Lavin 1991;Delbrouck et al 2002). Studies on galectin-1 expression in postnatal development of rat lung have indicated that translation and degradation are further levels of regulation by dexamethasone (Clerch et al 1987;Sanford et al 1993). Thus, galectin-1 expression observed in the preneoplastic clusters might be attributed to DES exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, multiple signalling pathways and enzymatic cascades are influenced by lectins. Therefore, it is not surprising that certain lectins are expressed in a developmentally regulated fashion, both during early embryonic 3 and postnatal development 4 . A subgroup of lectins is represented by the galectins [previously referred to as ‘S-type lectins’, emphasizing the activity dependence of some of them on thiols (reducing conditions)] 5 .…”
mentioning
confidence: 99%